Depriving out-of-school children of deworming tablets for soil-transmitted helminth infection in Bangladesh: the irony of a school-based deworming programme - Saha, Avijit; Chowdhury, Srizan; Goswami, Edwin Theophilus; Gop, Konica; Alam, Ariful; Rahman, Asadur; Sarker, Malabika (Tropical medicine and infectious disease, 2022)
Since 2008, Bangladesh has had a school-based deworming programme to combat soil-transmitted helminth (STH) infection among school-aged children (SACs). Existing programmes have trouble reaching SACs, especially those out-of-school (OSCs). This study evaluated deworming coverage among school going children (SGCs) and OSCs in two Nilphamari sub-districts. It also evaluated community knowledge on STH control and deworming coverage in both areas for all SACs. Saidpur (intervention) and Kishoregonj (control) sub-districts, in Nilphamari, were surveyed in December 2019. The survey included SACs and their parents. Among SGCs, the intervention group (89.0%) had higher deworming coverage than the control group (75.5%). In the intervention group, 59.9% of OSCs received the deworming tablet versus 24.6% in the control group. Community involvement activities including door-to-door visits, courtyard gatherings, and miking benefited both SACs and their primary caregivers. SACs living in the intervention region, awareness of the last pill distribution date, and caregivers observing BRAC workers in action, were linked to SAC deworming coverage. Re-strategizing the deworming programme to include the OSCs is vital and suggests timely action. Building community awareness and periodic epidemiological assessment can further facilitate an improved drug intake.